Correction to: Rare variants in KDR, encoding VEGF Receptor 2, are associated with tetralogy of Fallot (Genetics in Medicine, (2021), 10.1038/s41436-021-01212-y) - Skoric-Milosavljevic, Doris; Lahrouchi, Najim; Bosada, Fernanda M.; Dombrowsky, Gregor; Williams, Simon G.; Lesurf, Robert; Tjong, Fleur V. Y.; Walsh, Roddy; El Bouchikhi, Ihssane; Breckpot, Jeroen; Audain, Enrique; Ilgun, Aho; et al. (Genetics in Medicine, 2021)
Due to a processing error the author’s Doris Škorić-Milosavljević, Najim Lahrouchi, Alex V. Postma, Connie R. Bezzina were assigned to affiliation 38. However, affiliation 38 does not exist. In addition, the affiliations of Najim Lahrouchi, Elisabeth M. Lodder, and Connie R. Bezzina should be number 1 instead of number 2. The correct affiliation is Department of Clinical and Experimental Cardiology, Amsterdam University Medical Center, Amsterdam, The Netherlands. The original article has been corrected.
CRIS-Team Scopus Importer:2021-10-01